Paradoks czystości. Interpretacja oraz implikacje teologiczne słowa καθαρóς („czysty”) oraz καθαρóτης („czystość”) w Mdr 7,22-28 - Krawczyk, Mateusz (Collectanea Theologica, 2016)
The main purpose of the article is to carry out a research concerning the use of Greek words καθαρός (pure, clean) and καθαρότης (purity, cleanness) in one passage from the Book of Wisdom, namely Wis 7:22-28, and to find a solution to the observed paradox: purity beeing the condition and, at the same time, the result of man’s contact with Wisdom. Several research questions are posed, such as: Is it possible to associate the first use of the word with steam καθαρ (καθαρός; in v. 23) with man, or the author of the Book of Wisdom has in mind only immaterial beings? What is the relation between the purity of Wisdom in verse 24 and that from the previous verse? Can we interpret the text of the pericope 7,22-28 as follows: the Wisdom shares its ontological/moral purity with man? According to the author of the article, the answers to these questions may have a meaningful impact on the understanding of the theological thought of the Old as well as the New Testament. The method used consists, in the first place, in the analysis of the meaning of the discussed words (καθαρός; καθαρότης) in the most important Greek dictionaries/lexicons of classic Greek literature and Old/New Testament theology. Then, the focus shifts to the text of Wis 7:22-28 itself in its biblical context and synchronic analysis in which the text is studied in its final form is presented. The research leads to describing a contradiction concerning the purity of a man: being pure seems to be man’s condition for acquiring Wisdom, and, at the same time, man’s purity is the result of her acquisition. The proposed solution to this contradiction, or paradox, consists in the a priori influence of Wisdom on man, which does not relieve him from the effort to keep the state of purity.